Review: music, education and inclusivity:reflections and practices involved in making music (Orfeu, 2023)
The book with the title Música, educação e inclusão: reflexões e práticas para o fazer musical, [Music, education and inclusivity - reflections and practices involved in making music] was written by Lisbeth Soares and published in 2020. It is divided into six chapters and addresses questions about the relationship of music with culture, education, music teaching and the inclusive aspects of musical education . As well as discussions about conceptual issues, it includes suggestions about activities that are aimed at broadening the musical experiences of the students. The book represents a key publication and gives thought to a musical education that is significant and inclusive and can be put into practice.
Keywords: music; musical education; inclusivity; inclusive musical education